DO GREEN BRAND POSITIONING, GREEN BRAND KNOWLEDGE, ATTITUDE TOWARDS GREEN BRAND, AND ENVIRONMENTAL CONCERN ARE INFLUENCE FACTORS FOR THE GREEN PURCHASE INTENTION OF BLACK SOLDIER FLY LARVAE? - Dewana Traya Bagaskara; Lina Salim (STIE Pelita Nusantara Semarang, 2023)
The increasing number of human populations certainly has a bad influence on the environment. Food sources for humans also need a source of protein. For this reason, alternative protein sources are needed that can save threatened fish populations. This study is very simple, but the issue is very important for the environment. The purpose of this study is to determine the effect of green brand positioning, green brand knowledge, attitude towards green brand, and environmental concern on green purchase intention of black soldier fly larvae. The data used in this study is primary data obtained through distributing questionnaires to followers of Instagram (IG) Magalarva Tbk. The sample criteria in this study are 18-30 years old who know the Magalarva Tbk have never bought Magalarva products, and are domiciled in Greater Jakarta. The sampling method used is nonprobability sampling (purposive). All hypotheses are accepted. The results show that green brand positioning, green brand knowledge, attitude towards green brands, and environmental concerns have a significant effect on green purchase intention for the product of Magalarva’s brand.